Profiling and Imaging of Phospholipids in Brains of Abcd1‐Deficient Mice. Issue 1 (22nd February 2018) - Hama, Kotaro; Fujiwara, Yuko; Morita, Masashi; Yamazaki, Fumiyoshi; Nakashima, Yuko; Takei, Shiro; Takashima, Shigeo; Setou, Mitsutoshi; Shimozawa, Nobuyuki; Imanaka, Tsuneo; Yokoyama, Kazuaki
Abstract: ABCD1 is a gene responsible for X‐linked adrenoleukodystrophy (X‐ALD), and is critical for the transport of very long‐chain fatty acids (VLCFA) into peroxisomes and subsequent β‐oxidation. VLCFA‐containing lipids accumulate in X‐ALD patients, although the effect of ABCD1‐deficiency on each lipid species in the central nervous system has not been fully characterized. In this study, each phospholipid and lysophospholipid species in Abcd1 ‐deficient mice brains were profiled by liquid chromatography‐mass spectrometry. Among the phospholipid and lysophospholipid species that are significantly more enriched in Abcd1 ‐deficient mice brains, VLCFA were present in 75, 15, 5, 4, and 1 species of phosphatidylcholine, phosphatidylethanolamine, sphingomyelin, lysophosphatidylcholine, and lysophosphatidylethanolamine, respectively. Most VLCFA were incorporated at the sn ‐1 position of phosphatidylcholine and phosphatidylethanolamine. Among the phospholipid species that are significantly less enriched in Abcd1 ‐deficient mice brains, odd‐numbered saturated or mono‐unsaturated fatty acyl moieties are contained in all phosphatidylcholine species. In addition, a number of phosphatidylglycerol, phosphatidylinositol, and phosphatidylserine species contained highly unsaturated fatty acyl moieties. Intriguingly, 44:1 phosphatidylcholine with VLCFA was mainly distributed in the gray matter, such as the cortex, but not in the white matter in the cerebrum and cerebellum. These results show that ABCD1‐deficiency causes metabolic alternation of long‐chain fatty acids and VLCFA. Moreover, our results imply a molecular mechanism for the incorporation of saturated or monounsaturated VLCFA into the sn ‐1 position of phospholipids, and also indicate that the distribution of phospholipids with VLCFA may correlate with the development of X‐ALD.